2008
DOI: 10.1177/1352458507085801
|View full text |Cite
|
Sign up to set email alerts
|

Argentine Patagonia: prevalence and clinical features of multiple sclerosis

Abstract: There are few studies reporting multiple sclerosis prevalence rates in the Buenos Aires region, Argentina (latitude 34 degrees S) (between 12-18.5/100 000 inhabitants), and no studies have been performed in the larger region between parallels 36 degrees and 55 degrees S. The aim of this study is to determine the prevalence rates and clinical features of multiple sclerosis in residents of the Argentine Patagonia. Four cities from the region were selected for this study, giving a sample population of 417 666 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 15 publications
1
35
1
1
Order By: Relevance
“…Interestingly, a previous review of the prevalence of MS in Canada, which included several of the studies reported in the current review, found no striking evidence of a latitudinal or longitudinal gradient [4]. Similarly, Melcon et al [17] found no south-north gradient in prevalence within the Argentine Patagonia. Prevalence was much lower in South America compared to North America, despite the studied regions being similar distances from the equator.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, a previous review of the prevalence of MS in Canada, which included several of the studies reported in the current review, found no striking evidence of a latitudinal or longitudinal gradient [4]. Similarly, Melcon et al [17] found no south-north gradient in prevalence within the Argentine Patagonia. Prevalence was much lower in South America compared to North America, despite the studied regions being similar distances from the equator.…”
Section: Discussionmentioning
confidence: 55%
“…Nonetheless, current knowledge of MS epidemiology and economic burden comes from North American and European studies 9,10,12,13 . In Argentina, reported prevalence rates of MS range between 16 to 21 cases per 100,000 inhabitants 9,14,15 . Despite this information, the economic burden associated with the disease in Argentina as well as in the region of Latin America, is unknown.…”
mentioning
confidence: 99%
“…Estos datos, en general, concuerdan con los nuestros con dos salvedades: primero, nuestros pacientes son sólo EM-RR, condición necesaria para ingresar al programa de tratamiento; segundo, al comparar la sintomatología de debut de nuestros pacientes con países de latitud similar como Argentina y Brasil, tenemos algunas diferencias puesto que en ellos es más frecuente el inicio con NO, en tanto que nuestros pacientes presentaron manifestaciones sensitivas como manifestación inicial [18][19][20][21][22][23][24] . La Tabla 2 compara algunas características clínicas de nuestros pacientes en relación con otras series de latinoamericanas y latinos de Estados Unidos de Norteamérica.…”
Section: Resultsunclassified